Discrete-event system simulation - Banks, Jerry; Carson II, John S. ;Nelson, Barry L. ;Nicol, David M. (Upper Saddle River, New Jersey : Prentice-Hall, 2001)
This book provides a basic treatment of discrete-event simulation, one of the most widely used operations research and management science tools for dealing with system design in the presence of uncertainty. Proper collection and analysis of data, use of analytic techniques, verification and validation of models and the appropriate design of simulation experiments are treated extensively. Readily understandable to those having a basic familiarity with differential and integral calculus, probability theory and elementary statistics. Includes simulation in C++, the latest versions of the most widely used packages, and features of simulation output analysis software. Covers properties, modeling and random-variate generation from the lognormal distribution. Clarifies the difficult distinctions between terminating and steady-state simulation, and between within- and across-replication statistics. Contains up-to-date treatment of simulation of manufacturing and material handling systems. Emphasizes the hierarchical nature of computing systems, and how simulation techniques vary, depending on the level of abstraction. For readers wanting to learn more about system simulation.
CPU Simulation 557 -- 14.6 Memory Simulation 563 -- A.1 Random Digits 572 -- A.2 Random Normal Numbers 573 -- A.3 Cumulative Normal Distribution 574 -- A.4 Cumulative Poisson Distribution 576 -- A.5 Percentage Points of the Students t Distribution with v Degrees of Freedom 580 -- A.6 Percentage Points of the Chi-Square Distribution with v Degrees of Freedom 581 -- A.7 Percentage Points of the F Distribution with [alpha] = 0.05 582 -- A.8 Kolmogorov-Smirnov Critical Values 583 -- A.9 Maximum-Likelihood Estimates of the Gamma Distribution 584 -- A.10 Operating-Characteristic Curves for the Two-Sided t-Test for Different Values of Sample Size n 585 -- A.11 Operating-Characteristic Curves for the One-Sided t-Test for Different Values of Sample Size n 586.
Includes bibliographical references and index.
Keywords: SIMULATION METHODS